A modified scoring of the NCCN‐IPI is more accurate in the elderly and is improved by albumin and β2‐microglobulin - Melchardt, Thomas; Troppan, Katharina; Weiss, Lukas; Hufnagl, Clemens; Neureiter, Daniel; Tränkenschuh, Wolfgang; Hopfinger, Georg; Magnes, Teresa; Deutsch, Alexander; Neumeister, Peter; Hackl, Hubert; Greil, Richard; et al. (British journal of haematology, 2015)
Summary The International Prognostic Index (IPI) has been used for decades in diffuse large B‐cell lymphoma (DLBCL). A retrospective cancer registry analysis in North America showed significantly improved results when an enhanced IPI, the National Comprehensive Cancer Network (NCCN)‐IPI was applied. This novel score puts more weight on age and high levels of lactate dehydrogenase (LDH). Nevertheless, it remains unclear if these results can be extrapolated to the general population. This retrospective bi‐centre analysis included 499 unselected DLBCL patients who were treated with rituximab and anthracycline‐based chemoimmunotherapy between 2004 and 2013. In our cohort, the NCCN‐IPI was more accurate in identifying patients at low or high risk, despite older age, and more patients with increased LDH. Nevertheless, a modified scoring of the risk factors was required to more accurately identify elderly patients with a very favourable diagnosis, suggesting an impaired value of the original NCCN‐IPI in the elderly. Serum β2‐microglobulin and albumin were retained as independent prognostic factors for survival in a multivariate analysis. Our data confirm, for the first time, the superior prognostic power of the NCCN‐IPI in an unselected, middle‐European cohort. We furthermore propose a modified NCCN‐IPI for more accurate prognostication in the elderly. Albumin and β2‐microglobulin levels are likely to add significant information to the NCCN‐IPI.